(untitled) (Sustainability in Debate, 2013)
In Brazil, the development inter-municipal consortia were created to finance social infrastructure sector (health, sanitation, education) before being recognized through a constitutional amendment in 1998 and regulated by specific laws in 2005 and 2007. The territorial development policies are more recent; they began to be discussed in the late 1990s and implemented in the 2000s. This paper is structured based on two case studies and examines the origin of these policy tools, their complementarities and tensions, as well as the practices and strategies of the actors in the process implementation combined or parallel these two policies that mobilize similar references, but in different times.